Methological structure for the development of cities under uncertainty - Víctor G. Alfaro; Anna M. Gil (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Through the last year's global economical changes, population growth, and the need for allocation of resources towards population; have promoted the interest for the acceleration of economical regional development for the cities through new processes, some of which have to exceed the boundaries of the pre established paradigms, thus creative processes. The investigation presented in this paper pretends to apply administration models for the analysis and treatment of variables, which could exponentially rise the regional development of the Latin-American city of Morelia Michoacán, México. Accompanying the idea presented, we look forward to offer a proposal of investing economical resources towards the enhancement of the variables found, by assessing this action, we try to fill the gap that is found in the field of analyzing the process of optimal economic resource utilization for the development of cities. In order to achieve these tasks we will use tools for the treatment of fuzzy sets theory, evaluating related elements of the creative cities as a groundwork and economic impulse for the studied city. Results of the investigation are expected regarding the definition of the promoting activities, which will enhance the economical development of the city, and the replication in other cities is intended.
Keywords: 650; fuzzy logic; forgotten effects; creative process; regional development; creative cities